2007
DOI: 10.1002/jez.387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steroid hormones on Bufo arenarum oviduct. Ultrastructural study

Abstract: The endocrine regulation of the mucosa of the oviductal pars convoluta was analyzed by ultrastructural studies demonstrating that ovariectomy, together with a decrease in ovarian steroids circulating levels, caused a marked regression in this portion of Bufo arenarum oviduct. Twenty-five days after ovariectomy, a decrease in the depth of the epithelial and glandular layers was observed due to the notable loss of secretory cells, whose number was clearly smaller than in nonovariectomized females. The remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Confirming our results, previous data obtained by TEM (Winik et al ., 1999) demonstrated that the secretion contains abundant material of heterogeneous aspect constituted by SG released from the GSC and flocculent material from the ESC and that, although exocytosis still prevails, we can often observe processes of apocrine and holocrine secretion (Winik et al ., 1999; Medina et al ., 2000; 2007). That is to say that in this species the release of the contents that will form the structure of the jelly coats includes several mechanisms that have not been demonstrated in other amphibians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirming our results, previous data obtained by TEM (Winik et al ., 1999) demonstrated that the secretion contains abundant material of heterogeneous aspect constituted by SG released from the GSC and flocculent material from the ESC and that, although exocytosis still prevails, we can often observe processes of apocrine and holocrine secretion (Winik et al ., 1999; Medina et al ., 2000; 2007). That is to say that in this species the release of the contents that will form the structure of the jelly coats includes several mechanisms that have not been demonstrated in other amphibians.…”
Section: Discussionmentioning
confidence: 99%
“…At present, data concerning the histological organization of the PC in relation to the process of secretion of the jelly components are scarce. It is known that the IPZ, only described and partially studied in Rhinella arenarum (Moreno, 1972; Winik et al ., 1999; Medina et al ., 2007) and Rhinella paracnemis (Alcaide & Cruz López, 2002), represents a zone of morphological, structural and functional transition. Morphologically, in this region, the oviduct is no longer straight and the first convolutions appear, represented by the first two handles of the PPC (Moreno, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The apparition of the basolateral pump should take place during the postovulatory period, when the circulating concentrations of progesterone (P) are low, and androgens and estradiol (E 2 ) are high (Fernández et al, ; Medina et al, ), suggests that calcium pump is under estrogen regulation. Previous studies demonstrate that exogenous E 2 induces the development of the organoids that participate in the synthesis of numerous proteins, one of which could be the calcium pump (Fernández et al, ; Fernández and Ramos, ; Medina et al, ). Taken together, the present results demonstrate, for the first time in an amphibian that specific molecules participate both in the intracellular homeostasis of Ca 2+ and in the process of its secretion in the oviductal zone and thus implicated in the synthesis and secretion of jelly components.…”
Section: Discussionmentioning
confidence: 99%
“…In the toad Rhinella arenarum , as in other anuran amphibians, the oviducts are structurally and functionally divided into three main zones: the pars recta (PR), the pars convoluta (PC) and the ovisac or uterus (Moreno, ; Fernández et al, ; Winik et al, ; Medina et al, ). In these vertebrates, two types of oviductal secretion have been identified, each of them produced by a different portion of the duct and with a different biological role in fertilization.…”
mentioning
confidence: 99%
“…However, there are few studies that focus on the oviductal morphology of anurans and they are limited to some species and to some periods of the reproductive cycle (Shivers & James, 1970; Yoshizaki & Katagiri, 1981; Yoshizaki, 1985). Only the R. arenarum oviduct has been studied at the histological, ultrastructural and functional level throughout the reproductive cycle (Fernández et al , 1989; Winik et al , 1999; Fernández & Ramos, 2003; Medina et al , 2007; Crespo et al , 2009; Medina et al , 2012). With respect to L. chaquensis , at present the structural organization (Alcaide de Pucci, 1991b) and the histochemical analysis (Alcaide de Pucci, 1991a) of the oviduct during the preovulatory period have been studied by optical microscopy.…”
Section: Introductionmentioning
confidence: 99%